2022
DOI: 10.1007/s00204-022-03433-9
|View full text |Cite
|
Sign up to set email alerts
|

Fate of micronuclei and micronucleated cells after treatment of HeLa cells with different genotoxic agents

Abstract: Although micronuclei are well-known biomarkers of genotoxic damage, the biological consequences of micronucleus induction are only poorly understood. To further elucidate these consequences, HeLa cells stably expressing histone 2B coupled with green fluorescent protein were used for long-term live cell imaging to investigate the fate of micronuclei and micronucleated cells after treatment of cells with various genotoxic agents (doxorubicin (20, 30 and nM), tert-butyl hydroperoxide (tBHP, 50, 100 and 150 µM), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Although micronucleus is a well-known biomarker of genotoxic damage, little is known regarding the biological consequences of micronucleus induction. Reimann et al [ 39 ] found that the micronuclei did not share a common fate after treating HeLa cells with different genetic agents; however, DNA stability and micronucleus envelope were impaired, and LMNB1 was expressed in approximately 50% of the micronuclei. This finding indicated that micronucleus breakdown is required for chromosome fragmentation, while the damaged DNA is retained in the cell, which may promote tumor development [ 39 ].…”
Section: Lmnb1 and Malignant Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although micronucleus is a well-known biomarker of genotoxic damage, little is known regarding the biological consequences of micronucleus induction. Reimann et al [ 39 ] found that the micronuclei did not share a common fate after treating HeLa cells with different genetic agents; however, DNA stability and micronucleus envelope were impaired, and LMNB1 was expressed in approximately 50% of the micronuclei. This finding indicated that micronucleus breakdown is required for chromosome fragmentation, while the damaged DNA is retained in the cell, which may promote tumor development [ 39 ].…”
Section: Lmnb1 and Malignant Tumorsmentioning
confidence: 99%
“…Reimann et al [ 39 ] found that the micronuclei did not share a common fate after treating HeLa cells with different genetic agents; however, DNA stability and micronucleus envelope were impaired, and LMNB1 was expressed in approximately 50% of the micronuclei. This finding indicated that micronucleus breakdown is required for chromosome fragmentation, while the damaged DNA is retained in the cell, which may promote tumor development [ 39 ]. Nuclear membrane rupture is known to be associated with the loss or defect of lamin; however, the key physical determinants of nuclear membrane rupture remain unknown.…”
Section: Lmnb1 and Malignant Tumorsmentioning
confidence: 99%